KEKUATAN HUKUM MENGIKAT FATWA MUI NOMOR 18 TAHUN 2020 TERKAIT PENOLAKAN PROSES PEMAKAMAN JENAZAH POSITIF CORONA VIRUS DI KECAMATAN JATI ASIH, KOTA BEKASI. PERIODE MARET 2020- DESEMBER 2020 - Zulkifly Sanusi (2022)
The 2019 corona virus disease is an infectious disease that is currently endemic to the point of causing death. The problem in society today is the refusal to bury the bodies of patients suffering from this disease. MUI issued fatwas to help the public in dealing with existing problems related to the COVID-19 epidemic. The research aims to determine the application and regulation of the MUI Fatwa in connection with the burial of corpses who died as a result of COVID-19. Sociological juridical research type with a descriptive-analytic approach. The data taken consists of secondary data, in the form of primary legal materials, secondary legal materials and tertiary legal materials. In addition, as an analysis material, primary research data obtained from Jati Asih District was also used for the period of March 2020 - December 2020, where it is known that there are still many people who do not understand how to treat the bodies of patients infected with the COVID 19 virus. due to the absence of binding regulations regarding the handling of the bodies of COVID-19 patients and the lack of public knowledge regarding the handling of the bodies of patients infected with this virus. So that there is a need for binding regulations regarding the burial process of the bodies of COVID-19 patients.